Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai di Kantor Pertanahan Kota Ternate - Dina Lisani; Abdul Rahman Jannang (Jurnal Manajemen Sinergi, 2022)
Objective: The purpose of this study are: (1) Analyzing the influenceof Style Leadership on the Employee Performance of Ternate CityLand Office; (2) Analyzing the influence of Work discipline on theEmployee Performance of Ternate City Land Office; and (3)Analyzing the influence of style leadership and Work discipline asimultaneously on the Employee Performance of Ternate City LandOffice. The number of samples is 42 employees.Methodology: The test equipment used is multiple regressionanalysis using statistical package for social scientists (SPSS) as astatistical test tool.Finding: H1, H2, and H3 are accepted at the 5% confidence level.Conclusion: The results showed that: (1) Style Leadership has apositive and significant impact the Employee Performance ofTernate City Land Office. It is based on a t value greater than thevalue of t table, and a smaller significant value of alpha (Î±); (2) Workdiscipline has a positive and significant impact the EmployeePerformance of Ternate City Land Office. It is also based on a tvalue greater than the value of t table, and a significantly smallervalue of alpha (Î±); and (3) Style Leadership and Work disciplinesimultaneously have a positive and significant influence theEmployee Performance of Ternate City Land Office. It is based onthe F value count greater than the F table value, and the significantvalue smaller than alpha (Î±).